High Capacitance and Cycle‐Life Performance of a Binder‐Free Supercapacitor Nanocomposite Electrode by Direct Growth of Manganese Oxide Nanostructures on Carbon Nanotubes. Issue 8 (26th April 2017) - Ataherian, Fatemeh; Wang, Youling; Tabet‐Aoul, Amel; Mohamedi, Mohamed
Abstract: MnO x thin films with various oxidation states (MnO, Mn2 O3, MnO2 and mixed MnO/Mn3 O4 ) were directly grown onto carbon nanotubes by pulsed laser deposition under vacuum and at different oxygen partial pressures. The microstructural features of the as‐deposited thin films are characterized by scanning electron microscopy and X‐ray photoelectron spectroscopy. The electrochemical behavior of the CNT/MnOx nanocomposites in 1 M Na2 SO4 electrolyte is discussed with regards to specific capacitance, and cycle‐life, by means of cyclic voltammetry and electrochemical impedance measurements. First, at slow potential scan rate of 1 mV s −1, MnO x prepared under vacuum and 10 mTorr of O2 delivered specific capacitance as high as 738 and 653 F g −1, respectively. Second, the rate capability of these two nanocomposites over a wide range of scan rates showed that at 500 mV s −1, the former retained 93 % whereas the later displayed an increase of 1.2 % with regards to their respective initial specific capacitance values at 1 mV s −1 . They also maintained 90 % and 95 % of their specific capacitance after 10 000 continuous cycles with a 100 mV s −1 scan rate. The binder‐free nature of the CNT/MnO x nanocomposites and remarkable electrochemical properties suggest that these materials could find application as excellent electrodes for supercapacitors. Abstract : Let′s grow ! A binder‐free nanocomposite electrode was prepared by direct growth of manganese oxide nanostructures on carbon nanotubes. MnOx thin films with different oxidation states are grown onto carbon nanotubes at room temperature through pulsed laser deposition. These nanocomposites have potential application as electrodes for supercapacitors.